Mulheres da reforma agrária na educação: os significados em ser pedagoga da terra - Amaral, Débora Monteiro do (Universidade Federal de São Carlos, 2014)
This research investigated the professional activity of land-pedagogues graduated in the first year of the course Land Pedagogy in the state of Sao Paulo. It discussed the rural education and the struggles and efforts of social movements to certify that the education in the rural communities occurs with quality and respect to their culture. The aim of this research is to present what it meant to the personal and professional lives of graduates in Land Pedagogy at UFSCar to attend this course. Moreover, it aims to identify, describe and analyze the educational processes in the performance of these professionals as well as the ease and difficulties encountered by them. The methodology used was based on the principles of popular education, which engages social movements and breaks through the power relations aiming to fight the elitist hegemonic order settled in society. The oppressed and exploited subjects struggles for emancipation is within the social movements and within popular education. The theoretical and methodological background used were based on Paulo Freire and other authors of popular education, especially the books of Carlos Rodrigues Brandão. The data collection came about through a bibliographic survey concerning the topic and semi-structured individual interviews with 7 women egressed in the course. The data analysis occurred as a result of content analysis that revealed what this course meant to the personal and professional lives of its participants. The results shows some educational processes such as the awareness of these women who started to understand their life stories when they had the opportunity to deepen their studies on the agrarian context and rural education. This enabled them to possess new instruments to transform the reality in which they live. Through the reflexion between theory (content) and practice (life experience) they could also improve their performance as educators, becoming more critical in their work environments. The data indicates that these women increased their commitment to the settlement and the communities and feel responsible for collaborating with the people and contribute to the rural education. According to the data, one difficulty found by these women is the lack of paid work opportunities since there are no schools in the majority of the settlements that leads them to find jobs in the city where they cannot apply the knowledge about rural education acquired during their studies. It is revealed that to these women being a land-pedagogue means to believe that man and women are able to transform their lives through education and so transform the society where they live. This research shows that Land Pedagogy courses contribute to the qualifications of people in settlements and equips these people to return to their settlements and collaborate with the development of these communities.
Keywords: Educação rural; Educação do campo; Práticas sociais e processos educativos; Mulheres sem-terra; Pedagogia da terra; Educação popular; Educational processes; Women without land; Land pedagogy; Popular education; CIENCIAS HUMANAS::EDUCACAO